Molecular Characterization And Production Of A Specific Recombinant Protein Of Shigella Flexneri: Towards Development Of A Rapid Immunochromatography Diagnostic Test For Dysentery - Banga Singh, Kirnpal Kaur (2006)
Disenteri basilus atau juga dikenali sebagai shigelosis disebabkan terutamanya oleh bakteria Shigella.